Notch1 and Galectin-3 Modulate Cortical Reactive Astrocyte Response After Brain Injury - Ribeiro, Tais Novaki; Delgado-García, Lina Maria; Porcionatto, Marimelia A. (Frontiers in Cell and Developmental Biology, 2021)
After a brain lesion, highly specialized cortical astrocytes react, supporting the closure or replacement of the damaged tissue but fail to regulate neural plasticity. Growing evidence indicates that repair response leads astrocytes to reprogram, acquiring a partially restricted regenerative phenotype in vivo and neural stem cells (NSC) hallmarks in vitro. However, the molecular factors involved in astrocyte activation, the reparative response, and their relation to adult neurogenesis are poorly understood and remain an area of intense investigation in regenerative medicine. In this context, we addressed the role of Notch1 signaling and the effect of Galectin-3 (Gal3) as underlying molecular candidates involved in cortical astrocyte response to injury. Notch signaling is part of a specific neurogenic microenvironment that maintains NSC and neuroprogenitors, and Gal3 has a preferential spatial distribution across the cortex and has a central role in the proliferative capacity of reactive astrocytes. We report that in vitro scratch-reactivated cortical astrocytes from C57Bl/6J neonatal mice present translocation of Notch1 intracellular domain (NICD1) to the nucleus, indicating Notch1 activation. Colocalization analysis revealed a subpopulation of reactive astrocytes at the lesion border with colocalized NICD1/Jagged1 (Notch1 ligand) complexes compared with astrocytes located far from the border. Moreover, we found that Gal3 increased intracellularly, in contrast to its extracellular localization in non-reactive astrocytes, and NICD1/Gal3 pattern distribution shifted from diffuse to vesicular upon astrocyte activation. In vitro, Gal3-/- reactive astrocytes abolished Notch1 signaling at the lesion core. In addition, Notch1, Jagged1, and Delta-like1 were upregulated in C57Bl/6J reactive astrocytes, but not in Gal3-/- reactive astrocytes. Finally, we report that Gal3-/- mice submitted to a model of traumatic brain injury in the somatosensory cortex presented a disrupted response characterized by reduced number of GFAP reactive astrocytes, with smaller cell body perimeter and decreased NICD1 presence at the lesion core. These results suggest that Gal3 is essential to the proper activation of Notch signaling, facilitating the cleavage of Notch1 and nuclear translocation of NICD1 into the nucleus of reactive cortical astrocytes. Additionally, we hypothesize that the reactive astrocyte response is dependent on Notch1/Jagged1 signaling activation following brain injury.